Administering Accident Compensation in the 1980s - Rennie, Don (Victoria University of Wellington Law Review, 2003)
Having met its initial administrative challenges, ACC encountered serious political pressures in the turbulent economy of the 1980s. Pressure from employers to reduce costs, as well as controversies over lump-sum payments and other benefit levels, led to changes in entitlements, in conjunction with corporate reorganisation. This paper describes the shifts in organisational culture within ACC in the early 1980s and explains the fiscal consequences of the new “pay-as-you-go” funding formula. Even though formal reviews of the scheme paid homage to the original Woodhouse principles, the assumptions underlying these principles were losing ground in the face of economic tensions and eroding confidence in state-run programmes.